Managing traumatic testicular dislocations: what we know after two centuries - Sentilnathan Subramaniam; Muhammad Khairil Ab Khalil; Jasiah Zakaria; Firdaus Hayati (BMJ Publishing Group Ltd., 2020)
Traumatic testicular dislocation (TTD) is a rare consequence of blunt scrotal trauma. A 21-year old gentleman presented with inguinal pain following a motorcycle accident and physical examination revealed absence of both testes within a well-formed scrotal sac with bilateral inguinal swellings. Ultrasonography confirmed viability and location of the testes at the superficial inguinal pouch. He underwent emergent surgical reduction with orchidopexy and was discharged the next day. No evidence of testicular dysfunction or atrophy was noted at follow-up. We reviewed reports of TTDs reported in English over the last two centuries and discuss its occurrence, evolution and management